EFL Students’ Digital Skill Challenges during Online Service Learning - Lumiati, Lumiati; Nurfaidah, Sitti; Pehala, Ilfan Askul; Syukri, Suhartini; Abidin, Azwar (IAIN KENDARI, 2024)
This study aims to explore the challenges faced by EFL students when creating digital content during online service learning amidst the Covid-19 pandemic. Six students from the English Education Department at a higher education institution in Southeast Sulawesi participated in this study, selected based on their involvement in online service-learning activities during the pandemic. Data were collected through reflective journals. The findings revealed that participants encountered various internal and external challenges. Internal challenges included technical issues such as difficulties in memorizing scripts, editing videos, selecting suitable editing applications, designing thumbnails, and creating captions, all requiring creativity. Situational internal challenges involved filming independently, selecting appropriate content, engaging effectively in collaboration, and managing publicity. Emotional challenges encompassed uncertainty about starting the video production process and maintaining patience during the content creation. External technical issues included unstable internet connections and limited camera storage. Situational external challenges involved environmental noise, poor weather conditions, and the requirement to independently produce ten content videos.